2009
DOI: 10.1016/j.cub.2009.02.021
|View full text |Cite|
|
Sign up to set email alerts
|

Microtubule-Associated Kinase-like Protein RUNKEL Needed for Cell Plate Expansion in Arabidopsis Cytokinesis

Abstract: Cytokinesis partitions the cytoplasm of dividing eukaryotic cells. In higher plants, a dynamic microtubule array--phragmoplast--mediates the formation of the partitioning membrane--cell plate--in a centrifugal fashion. This phragmoplast dynamic involves microtubule-associated proteins. Mutations in a novel Arabidopsis gene RUNKEL (RUK) result in cytokinesis defects caused by abnormal phragmoplast organization and arrested cell plate expansion. RUK encodes an essential cell-cycle-regulated 152 kDa protein with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Endosperm defective 1 (AT2G44190; c44482_g1_i1) is a microtubule-associated protein, essential for cell division of embryo and endosperm82. RUNKEL (AT5G18700; c50689_g1_i1) is responsible for phragmoplast organization and cell plate expansion83. ALTERED MERISTEM PROGRAM 1 (AT3G54720; c47383_g5_i1 & c48054_g2_i2) regulates pollen tube attraction by synergid cells84.…”
Section: Resultsmentioning
confidence: 99%
“…Endosperm defective 1 (AT2G44190; c44482_g1_i1) is a microtubule-associated protein, essential for cell division of embryo and endosperm82. RUNKEL (AT5G18700; c50689_g1_i1) is responsible for phragmoplast organization and cell plate expansion83. ALTERED MERISTEM PROGRAM 1 (AT3G54720; c47383_g5_i1 & c48054_g2_i2) regulates pollen tube attraction by synergid cells84.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, previous functional studies of plant PKs indicated that these PK genes within conserved exon-intron structures function as core components of various signaling pathways that control multiple plant cellular processes. (1) Mitosis: Aur [ 51 ] and ULK_ULK4 [ 52 ] function in cell division in A . thaliana .…”
Section: Discussionmentioning
confidence: 99%
“…4b–d), suggesting that the AtNACK1-GFP protein has a dominant-inhibitory effect on wild-type AtNACK1 in the transgenic plants. The Arabidopsis mutation of RUNKEL exhibits severe cytokinetic defects and results in seedling lethal (Krupnova et al 2009). Recently, it has been reported that the transgenic plants expressing truncated RUNKEL proteins cause the mislocalization of Myc-AtNACK1/HIK, such that it is dispersed around the cell plate and between the daughter nuclei from early to late stages of cytokinesis in these plants (Krupnova et al 2013).…”
Section: Discussionmentioning
confidence: 99%